The exploitation of vulnerability through personalised marketing communication: Are consumers protected? - Joanna Strycharz; Bram Benjamin Duivenvoorde (Internet Policy Review, 2021)
While data-driven personalisation strategies in marketing offer consumers several benefits, they potentially also create new disparities and vulnerabilities in society, and in individuals. This article explores in what ways application of so-called personalised marketing communication may lead to exploitation of vulnerability of consumers and builds on empirical findings on the issue by investigating if consumers are protected against such vulnerabilities under EU consumer protection law. We show a number of ways in which personalisation may lead to exploitation of internal and external vulnerabilities and that EU consumer law contains significant barriers to effectively address such exploitation.
Keywords: 300; Personalisation; Consumer protection; Consumer rights